Hygro-thermal vibrations and buckling of laminated nanoplates via nonlocal strain gradient theory. (15th April 2021) - Tocci Monaco, Giovanni; Fantuzzi, Nicholas; Fabbrocino, Francesco; Luciano, Raimondo
Abstract: Vibrations and buckling of thin laminiated composite nano plates in hygrothermal environment are investigated using second-order strain gradient theory. Hamilton's principle is used in order to carry out motion equations. To obtain analytical solution Navier displacement field has been considered for both cross- and angle-ply laminates. Numerical solutions are provided and discussed in terms of plate aspect ratio and non local ratio for a large number of laminates. Whenever possible a comparison with classical analytical solutions is reported for buckling loads and fundamental frequencies. This work shows a large variety of angle-ply cases which are not common in the published literature. Moreover, critical temperatures for cross- and angle-ply laminates are shown for buckling and free vibration analyses.